Pelatihan E-Commerce Berbasis Praktik sebagai Upaya Meningkatkan Kompetensi Digital Guru SMK Negeri 1 Woyla - Nadlia Ariyati; Desi Yuliana; Muhammad Rezaldi; Tamitha Intassar Husen (Universitas Teuku Umar, 2026)
This community service project responds to the growing need to enhance teachers’ digital competence amid the rapid expansion of the digital economy, particularly in e-commerce. Implemented at SMK Negeri 1 Woyla, the program involved 14 teachers and adopted a participatory training approach, including pre-test, interactive sessions, discussions, hands-on practice, and post-test evaluation. The training focused on e-commerce concepts, marketplace utilization, and digital marketing practices. Initial results indicated that participants had a moderate level of theoretical understanding but limited practical experience, especially in using marketplace platforms. Following the training, there was a clear improvement in both knowledge and practical skills, reflected in the successful creation of marketplace accounts and increased confidence in applying digital tools. Overall, the program effectively strengthened teachers’ digital competencies and supported the integration of e-commerce into vocational learning.